Novel nanocarbon materials for different applications - Z. Mansurov (ՀՀ ԳԱԱ հրատ.)
This paper reviews recent results in the field of novel nanocarbon materials research obtained in the Combustion Problem Institute and their practical applications. They are: sorption of gold and ion of heavy metals by carbonized apricot stones, mechanochemical encapsulation of quartz particles in metal carbon films, novel carbon materials for battery application, multifunctional catalysts of oil hydrofining, carbon containing refractories, fullerens and nanotubes formation during hydrocarbons combustion.
Keywords: Քիմիա